2002
DOI: 10.1080/1071576021000016463
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Flavonoids with Iron and Copper Ions: A Mechanism for their Antioxidant Activity

Abstract: The metal chelating properties of flavonoids suggest that they may play a role in metal-overload diseases and in all oxidative stress conditions involving a transition metal ion. A detailed study has been made of the ability of flavonoids to chelate iron (including Fe3+) and copper ions and its dependence of structure and pH. The acid medium may be important in some pathological conditions. In addition, the ability of flavonoids to reduce iron and copper ions and their activity-structure relationships were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
558
2
20

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 867 publications
(629 citation statements)
references
References 49 publications
34
558
2
20
Order By: Relevance
“…Some results showed that AST protected neuronal cells against oxidative damage, and thus it has been a potent candidate for brain food (Liu and Osawa, 2009), and additionally could protect PC12 cells against glucose toxicity (Zhang et al, 2015). On the other hand, Cu 2+ could lead to various cell injuries by inducing oxidative stress and mitochondrial dysfunction (Murphy and Taiz, 1997;Mira et al, 2002;Ma et al, 2014). Cu 2+ -induced production of hydrogen peroxide and hydroxyl radicals has been directly correlated with the damage to proteins and lipids .…”
Section: Discussionmentioning
confidence: 99%
“…Some results showed that AST protected neuronal cells against oxidative damage, and thus it has been a potent candidate for brain food (Liu and Osawa, 2009), and additionally could protect PC12 cells against glucose toxicity (Zhang et al, 2015). On the other hand, Cu 2+ could lead to various cell injuries by inducing oxidative stress and mitochondrial dysfunction (Murphy and Taiz, 1997;Mira et al, 2002;Ma et al, 2014). Cu 2+ -induced production of hydrogen peroxide and hydroxyl radicals has been directly correlated with the damage to proteins and lipids .…”
Section: Discussionmentioning
confidence: 99%
“…According to way (I), organic ligands at higher pH values can chelate iron completely (60)(61)(62) , changing the redox potential of Fe 2+ /Fe 3+ pair (E°=+0.771 V) (63) . Considering the way (II) and highlighting that the first transition period are labile, following a dissociative mechanisms (S N 1) (64) .…”
Section: Ligands Effects On Fenton Reactionmentioning
confidence: 99%
“…Furthermore, the orthohydroxyphenoxy radical produced from the oxidation of a catechol/pyrogallol moiety can also react with a second freeradical species, including 3 O 2 , to afford oxidizing orthoquinones and O 2 À. (59). Because of these reactions, the catecholic betel phenolic compounds like hydroxychavicol and ChA (Fig.…”
Section: Betel Nutraceuticals Offer Chemopreventive Benefits: Potentimentioning
confidence: 99%